GRAFIK MA`LUMOTLAR BILAN ISHLASHDA C++ IMKONIYATLARIDAN FOYDALANISH - Alaminov, M.; O’razboyev, N.; Qunnazarov, O. (SCIENCE and SOCIETY, 2017)
The article is devoted to the study of the technique of using of possibilities of a programming language C++ in the work with the graphic information. The functions to drawing graphics in programming language C++ are used. The application of this functions was explained with the two programs.